Uncinula necator (Schow) Burr., the Causal Agent of Grape Powdery Mildew: Infection Potential and Microclimate - Zoran Miladinović; Petar Vukša; Novica Miletić (Pesticidi i Fitomedicina, 2007)
Microclimate in Podgorica vineyards and its effect on the formation, maturing and rupturing of cleistothecia, and disease outbreak, was studied. An analysis of collected data on minimum and maximum temperatures and precipitation over the periods November-April (2001/2002, 2002/2003 and 2003/2004) and April-July (2002, 2003 and 2004) and their comparison with the average values over a 50-year period, indicate that neither temperature nor precipitation act as a limiting factor for disease outbreak and development in Podgorica vineyards. Over the trial period, conditions were favourable for the formation and maturing of cleistothecia between November and April. Asum of 1100ºC mean daily temperature was reached by mid-March.From bud burst to end of vine flowering, the conditions were again nearly optimal both for ascospore release from cleistothecia and primary infection, and for secondary infection. Initial symptoms appeared on lower leaves and inflorescences. Cleistothecia appeared inall green parts of grapevine. In 2002, and 2004, conditions were favourable for a secondary infection of bunches, leaves and canes from April to mid-July. Conditions for secondary infection were less favourable in the second half of June 2003. That year was characterized by warmer weather with less rainfall, especially in June and July. In 2004, precipitation and temperature were lower than in 2002, which resulted in a slightly less severe outbreak of disease.